Blog : un journal intime comme mémoire de soi - Nolwenn Hénaff (Conserveries Mémorielles)
Keeping a journal has become a way of live, or to moment a moment in one’s life (Lejeune, 2006). It has multiple uses: construction of a narrative identity, marking time, liberating the self, introspection, self-control, self-support, organization of thoughts or the pleasure of writing. If paper writing is still the most common form of biographical narrative, other media like television or radio have offered new areas of experimentation with these stories of self. More recently, the advent of the Internet and its easy publishing tools have triggered the emergence of innovative biographical forms. Yet, whether to overcome a crisis, keep the memory of a powerful experience, or, more generally, recount his travels and his vacation, the journal is positioned above all as a space of freedom: one writes when one wants to and the way she wants to. The "Care of the Self" as Foucault would say, the space dominated by sensations, and temporality marked by the concept of moments that express a personal connotation are clues revealing the private practice of writing in line. Blog appear at crucial moments in life and often accompanies the biographical turning points (breaks and self-questionings but also new discoveries and new friends). This paper proposes an analysis of blogs as media of personal memory and studies examples of strategies developed by bloggers in order to create through this innovative communicational device an "area of ​​canning home" online.